A contact terminal containing a high-thickness gold layer and a method for manufacturing the same

CN122907942APending Publication Date: 2026-10-13WANMING ELECTROPLATING INTELLIGENT TECH (DONGGUAN) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611315402.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-27
Publication Date
2026-10-13

Smart Images

  • Figure CN122907942A_ABST
    Figure CN122907942A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of electric switch, and discloses a contact terminal containing a high-thickness gold layer and a preparation method thereof. The preparation method comprises the following steps: after surface treatment of a terminal base material, the terminal base material is placed in a nickel plating solution to perform nickel plating treatment by using a gradient current method, so as to obtain a pretreated base material containing a nickel layer, wherein the current density in the gradient current method increases with the increase of the thickness of the nickel layer; a resin insulating material is coated on a non-gold plating area of the pretreated base material containing the nickel layer, so as to obtain a gold plating base material; the gold plating base material is placed in a gold plating solution to perform gold plating treatment, and after the gold plating is completed, the insulating protective layer is removed, so as to obtain a contact terminal containing a high-thickness gold layer, wherein the gold plating solution comprises at least one of a nitrogen-containing heterocyclic compound, a sulfonate compound and a polyol compound. The contact terminal containing the gold layer with a thickness of more than or equal to 30u" can be applied to the field of electric switch, effectively improves the compactness of the gold layer, and effectively reduces the overall resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of electrical switch technology, specifically to a contact terminal with a high-thickness gold layer and its preparation method. Background Technology

[0002] In electronic devices, contact terminals, as crucial components for circuit conduction and signal transmission, are widely used in electrical switches, relays, and various electrical connectors. They transmit current through mechanical contact between the terminal contact areas. In existing technologies, copper alloys are typically used as the terminal substrate, with a nickel barrier layer deposited on its surface followed by a gold layer. This leverages gold's excellent conductivity, chemical stability, and oxidation resistance to reduce the risk of oxidation at the contact interface and extend the terminal's lifespan. Especially in high-frequency insertion / removal and high-reliability electrical connection scenarios, using a thicker gold layer (i.e., Au ≥ 30u″) can further enhance the wear resistance of the contact area, reducing substrate exposure due to wear during long-term use and thus maintaining lower contact resistance.

[0003] However, during the continuous electrodeposition of thick gold layers, as the deposition thickness increases, gold grains gradually grow epitaxially along existing grains and coarsen, easily forming columnar crystal structures. This makes it difficult for grain boundary defects, dislocations, and vacancies to be released in a timely manner, resulting in the continuous accumulation of residual stress inside the coating. This leads to defects such as microcracks and local porosity in the gold layer. At the same time, grain coarsening and preferential growth reduce the uniformity of the coating structure, increase the number of grain boundary gaps and micropores, and reduce the density of the gold layer. This reduces its ability to protect the nickel layer and copper substrate, ultimately leading to an increase in the contact resistance of the contact terminals and affecting their performance. Summary of the Invention

[0004] The technical problem to be solved by the present invention is to provide a contact terminal with a high-thickness gold layer and a method for preparing the same, in order to solve the problem that the resistance of the gold plating layer increases due to increased internal stress and decreased density when the thickness of the gold plating layer is increased in the contact terminal.

[0005] To address the aforementioned technical problems, a method for fabricating contact terminals containing a high-thickness gold layer is proposed. This method includes the following fabrication steps: S1. After surface treatment of the terminal substrate, it is placed in a nickel plating solution and nickel plating is performed using a gradient current method to obtain a pretreated substrate containing a nickel layer. In the gradient current method, the current density increases with the increase of the nickel layer thickness. S2. Coat the non-gold-plated areas of the pretreated substrate containing a nickel layer with a resin insulating material to obtain the substrate to be gold-plated. S3. The substrate to be gold-plated is placed in the gold plating solution for gold plating treatment. After the gold plating is completed, the insulating protective layer is removed to obtain a contact terminal with a high-thickness gold layer. The gold plating solution includes at least one of nitrogen-containing heterocyclic compounds, sulfonate compounds, and polyol compounds.

[0006] In addition, a contact terminal with a high-thickness gold layer is also provided, which is prepared by the above-described method for preparing a contact terminal with a high-thickness gold layer.

[0007] As can be seen from the above technical solutions, the exemplary embodiments disclosed herein possess at least the following advantages and positive effects: On the one hand, by employing a technique of coating non-gold-plated areas of a pretreated substrate containing a nickel layer with resin insulating material and removing the insulating protective layer after gold plating, the resin insulating material can form a continuous and dense bonding interface with the nickel layer surface. This effectively blocks the penetration and migration of the gold plating solution along the interface between the insulating protective layer and the nickel layer, avoiding the phenomenon of missed plating caused by bonding gaps, positioning deviations, and edge lifting of the physical mask. This solves the problem of abnormal gold deposition in non-gold-plated areas due to poor bonding of the physical mask in the prior art, thereby achieving the technical effects of improving the accuracy of local gold plating boundaries, reducing boundary defects, and improving the long-term conductivity stability of the contact terminals.

[0008] On the other hand, by employing a gradient current method for nickel plating and using a gold plating solution containing at least one of nitrogen-containing heterocyclic compounds, sulfonate compounds, and polyol compounds, the gradient current method gradually increases the current density, causing the nickel layer to form uniform and fine crystal nuclei from a low current stage, followed by continuous growth through a medium-to-high current stage, resulting in a dense nickel layer with refined grains, uniform thickness, and a smooth surface, providing a stable deposition substrate for a thick gold layer. Simultaneously, nitrogen-containing heterocyclic compounds, sulfonate compounds, and polyol compounds all possess polar functional groups and electron-rich active sites, which, during cathodic polarization... It can preferentially adsorb onto the newly formed gold deposition interface through electron donor-acceptor interactions, forming a dynamic adsorption layer that selectively covers the cathode active sites, regulates the discharge reduction rate and surface diffusion behavior of gold ions, inhibits abnormal grain growth caused by local rapid deposition, and reduces the accumulation of residual internal stress during high-thickness deposition. This promotes the continuous formation of a fine-grained, continuous, and dense microstructure in the gold plating layer, further overcoming the problem of increased internal stress and decreased density in high-thickness gold plating layers leading to increased contact resistance. It achieves the technical effect of high density and low contact resistance in high-thickness gold layers, improving the conductivity of contact terminals. Attached Figure Description

[0009] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this disclosure and, together with the description, serve to explain the principles of this disclosure. It is obvious that the drawings described below are merely some embodiments of this disclosure, and those skilled in the art can obtain other drawings based on these drawings without any inventive effort. In the drawings: Figure 1 This is a schematic diagram of a method for preparing a contact terminal containing a high-thickness gold layer in one embodiment; Figure 2 This is a schematic diagram of step S1 in a method for preparing a contact terminal containing a high-thickness gold layer in one embodiment; Figure 3 This is a schematic diagram of step S2 in a method for preparing a contact terminal with a high-thickness gold layer in one embodiment; Figure 4 This is a schematic diagram of step S3 of a method for preparing a contact terminal with a high-thickness gold layer in one embodiment, which uses a nitrogen-containing heterocyclic compound. Figure 5 This is a schematic diagram of step S3 of a method for preparing a contact terminal containing a high-thickness gold layer in one embodiment, which uses a sulfonate compound. Figure 6 This is a schematic diagram of step S3 of a method for preparing a contact terminal containing a high-thickness gold layer in one embodiment, which uses a polyol compound. Figure 7 This is a front view of a contact terminal containing a thick gold layer; Figure 8 This is a schematic diagram of the back side of a contact terminal containing a thick gold layer. Detailed Implementation

[0010] Exemplary embodiments will now be described more fully with reference to the accompanying drawings. However, these exemplary embodiments can be implemented in many forms and should not be construed as limited to the examples set forth herein; rather, these embodiments are provided so that this disclosure will be more thorough and complete, and will fully convey the concept of the exemplary embodiments to those skilled in the art.

[0011] Furthermore, the described features or characteristics may be combined in any suitable manner in one or more embodiments. Numerous specific details are provided in the following description to give a thorough understanding of embodiments of this disclosure. However, those skilled in the art will recognize that the technical solutions of this disclosure may be practiced without one or more of the specific details, or other methods, steps, etc. may be employed. In other instances, well-known methods, implementations, or operations are not shown or described in detail to avoid obscuring various aspects of this disclosure.

[0012] The flowcharts shown in the accompanying drawings are merely illustrative and do not necessarily include all content and operations / steps, nor do they necessarily have to be performed in the described order. For example, some operations / steps can be broken down, while others can be combined or partially combined; therefore, the actual execution order may change depending on the specific circumstances.

[0013] Please refer to Figure 1 This invention proposes a method for preparing a contact terminal containing a high-thickness gold layer, the method comprising the following preparation steps: S1. After surface treatment of the terminal substrate, it is placed in a nickel plating solution and nickel plating is performed using a gradient current method to obtain a pretreated substrate containing a nickel layer. In the gradient current method, the current density increases with the increase of the nickel layer thickness.

[0014] In step S1, the terminal substrate is a copper alloy substrate, and the nickel plating solution consists of 150~300g / L of nickel salt, 25~40g / L of boric acid, 20~50g / L of citric acid, and the remainder of deionized water. The nickel salt includes at least one of nickel aminosulfonate, nickel sulfate, and nickel chloride.

[0015] By using a lower current density in the initial stage of nickel layer deposition, nickel atoms are uniformly nucleated on the surface of the terminal substrate, forming a nickel layer with fine grains and fewer defects. As the nickel layer thickness increases, the current density is increased, allowing nickel atoms to continuously fill the voids inside the nickel layer, improving the density of the nickel layer structure. This provides a uniform and continuous growth interface for subsequent gold layer deposition, enabling gold ions to be uniformly reduced on the nickel layer surface and form stable gold nuclei. This reduces the localized rapid growth and defect accumulation of the gold layer caused by surface defects and activity differences in the nickel layer, solving the problem of increased gold layer deposition defects due to uneven nickel layer in the prior art, thereby achieving the technical effect of improving the uniformity of gold layer deposition.

[0016] Step S1 includes: S1.1 Place the terminal substrate in an alkaline degreasing solution and degrease it at 50~70℃ for 3~10 minutes, then wash it with water to obtain a degreased terminal. The alkaline degreasing solution is composed of 10~30g / L sodium hydroxide, 20~60g / L sodium carbonate, 0.5~3g / L surfactant and the balance deionized water. The surfactant includes at least one of fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, sodium dodecyl sulfate and sodium dodecylbenzene sulfonate.

[0017] The terminal substrate is placed in an alkaline degreasing solution for degreasing treatment. Sodium hydroxide and sodium carbonate are used to saponify, emulsify, and disperse the grease, stamping lubricant, and organic contaminants on the terminal surface, so that the organic residues adhering to the substrate surface can be fully detached from the substrate. At the same time, the surfactant can reduce the surface tension of the degreasing solution, improve the wettability and penetration ability of the degreasing solution on the terminal surface, and enable the degreasing solution to enter the micropores, scratches and tiny depressions on the terminal surface. It can encapsulate and stably disperse the contaminants that are difficult to remove in the degreasing solution, and prevent the contaminants from redepositing on the terminal surface. As a result, a degreased terminal with a clean surface, fully exposed active sites, and uniform surface energy is obtained.

[0018] S1.2 Place the degreased terminals in the activation solution and activate them at room temperature for 30~120s. Wash with water to obtain activated terminals. The activation solution is a deionized aqueous solution containing 10~20 vol% hydrochloric acid or 5~15 vol% sulfuric acid.

[0019] The degreased terminals are placed in an activation solution for activation treatment. Hydrochloric acid or sulfuric acid is used to remove the natural oxide film, passivation layer and inorganic impurities on the terminal surface, so that the clean metal substrate is fully exposed. At the same time, the terminal surface is slightly and uniformly etched to form uniformly distributed micro-active sites, which improves the surface energy, electrochemical activity and interface cleanliness of the terminal surface, resulting in activated terminals with high surface activity, uniform distribution of active sites and no oxide layer coverage.

[0020] S1.3. Place the activated terminal in a nickel plating solution with a temperature of 45~55℃ and a pH of 3.8~4.5, at a flux of 0.5~1.5A / dm³. 2 The current density was deposited to a nickel layer thickness of 10~30 μ″, and then the current density was increased to 1.5~2.5 A / dm. 2 The temperature of the nickel plating bath was controlled to rise to 50-60℃, and deposition continued until the nickel layer thickness reached 30-80 μm; finally, the current density was increased to 3.0-5.0 A / dm². 2 The temperature of the nickel plating solution is raised to 55~65℃, and deposition continues until the total thickness of the nickel layer reaches 50~150µ″, thus obtaining a pretreated substrate containing a nickel layer.

[0021] In the initial stage of nickel plating, a lower current density and lower temperature are used to maintain a moderate cathode reduction rate of nickel ions, promoting uniform nucleation of nickel atoms on the activated terminal surface and forming a fine and uniformly distributed initial nickel layer. As the nickel layer thickness increases, the current density and plating bath temperature are gradually increased to improve the mass transfer efficiency of nickel ions and the cathode deposition rate, allowing subsequent nickel atoms to preferentially grow continuously along the already formed crystal nuclei. This ensures deposition efficiency while suppressing local abnormal growth and reducing dendrites, porosity, and coarse grain structures caused by excessively rapid deposition rates. Finally, a thick nickel layer is deposited under higher current density and higher temperature conditions. The uniform crystal nuclei and continuous grains formed in the early stage serve as a growth framework, ensuring stable epitaxial growth of the newly added nickel layer. This avoids problems such as cracks, warping, and decreased adhesion caused by rapid accumulation of internal stress during the thick nickel layer deposition process, providing a stable plating foundation for the terminals.

[0022] S2. Coat the non-gold-plated areas of the pretreated substrate containing the nickel layer with resin insulating material to obtain the substrate to be gold-plated.

[0023] The resin insulation material in step S2 includes at least one of polyurethane resin, epoxy resin, and acrylic resin.

[0024] During the process of increasing the thickness of the gold plating layer on the contact terminals, if the shielding effect of the non-gold-plated areas is insufficient, the gold complex ions in the gold plating solution can easily penetrate and migrate along the interface between the insulating protective layer and the nickel layer, resulting in incomplete plating in the non-contact areas, irregular gold plating boundaries, and affecting the wear resistance and contact resistance stability of the gold layer in the contact area. By coating the non-gold-plated areas with at least one resin insulating material selected from polyurethane resin, epoxy resin, and acrylic resin, the good wetting and spreading ability of the resin on the activated nickel layer surface is utilized to allow the resin to fully fill the micro-undulation structure of the nickel layer surface. Relying on the strong interfacial adsorption between the polar functional groups in the resin molecules and the nickel layer surface, the adhesion of the resin insulating material to the nickel layer is improved, forming a continuous and dense bonding interface, blocking the penetration and migration of the gold plating solution along the interface, and improving the boundary shielding effect.

[0025] Step S2 includes: S2.1 Add the resin insulating material and curing agent to an organic solvent and stir at 25~40℃ and 300~600rpm to dissolve them, thereby obtaining a resin coating liquid. The organic solvent includes at least one of acetone, butanone, and anhydrous ethanol. The mass ratio of the resin insulating material to the organic solvent is 1:(1~2). The curing agent includes at least one of amine curing agent, isocyanate curing agent, and light curing agent. The amount of curing agent added is 1~15wt% of the mass of the resin insulating material.

[0026] The resin insulating material and curing agent are added to an organic solvent and stirred to dissolve. The organic solvent dissolves and disperses the resin molecular chains, allowing the resin insulating material to fully expand and be uniformly dispersed in the system. At the same time, the curing agent is uniformly distributed in the resin system, avoiding resin agglomeration and local enrichment of the curing agent. This results in a resin coating liquid with uniform composition, stable viscosity, good fluidity, and consistent dispersion of each component.

[0027] S2.2 Apply the resin coating liquid to the non-gold plating area of ​​the pretreated substrate containing the nickel layer and cure it to obtain the substrate to be gold plated. The coating thickness of the resin coating liquid is 20~40μm.

[0028] When the resin insulation material is polyurethane resin, the curing agent is an isocyanate curing agent, and the amount of isocyanate curing agent added is 5~15wt% of the mass of polyurethane resin. The isocyanate curing agent is hexamethylene diisocyanate trimer and / or isophorone diisocyanate trimer. The curing treatment is a heat curing treatment, with a curing temperature of 60~120℃ and a curing time of 30~90min.

[0029] When the resin insulation material is epoxy resin, the curing agent is an amine curing agent. The amount of amine curing agent added is 5~15wt% of the epoxy resin mass. The amine curing agent includes at least one of ethylenediamine, diethylenetriamine, triethylenetetramine, and isophoronediamine. The curing treatment is a heat curing treatment with a curing temperature of 80~150℃ and a curing time of 30~120min.

[0030] When the resin material is acrylic resin, the curing agent is a UV curing agent, and the amount of UV curing agent added is 1-8 wt% of the acrylic resin mass. The UV curing agent includes at least one of photoinitiator 1173, photoinitiator 184, and photoinitiator 819. The curing treatment is ultraviolet curing, with an ultraviolet wavelength of 365-405 nm and a light intensity of 200-1000 mW / cm². 2 The curing time is 30~300s.

[0031] By curing the resin coating liquid applied to the non-gold-plated area, the active groups in the polyurethane resin, epoxy resin, or acrylic resin undergo a cross-linking reaction under the action of the corresponding curing agent, forming a three-dimensional cross-linked network structure. This transforms the resin from a liquid state into a continuous and dense solid insulating protective layer. The cross-linked resin molecular chains entangle with each other and form a stable network, reducing the internal free volume of the resin and improving the structural integrity, mechanical strength, and chemical corrosion resistance of the coating. At the same time, it enhances the adhesion of the resin to the nickel layer surface, enabling the resin insulating material and the nickel layer to form a continuous, dense, and firmly bonded interface. This results in a gold-plated substrate with complete boundaries, a stable interface, and good insulation and barrier properties.

[0032] S3. The substrate to be gold-plated is placed in the gold plating solution for gold plating treatment. After the gold plating is completed, the insulating protective layer is removed to obtain a contact terminal with a high-thickness gold layer. The gold plating solution includes at least one of nitrogen-containing heterocyclic compounds, sulfonate compounds, and polyol compounds.

[0033] In step S3, the nitrogen-containing heterocyclic compound includes at least one of imidazole, pyrazole, and triazole; the sulfonate compound includes at least one of sodium hydroxyethanesulfonate, sodium methanesulfonate, sodium ethanesulfonate, and sodium propanesulfonate; and the polyol compound includes at least one of ethylene glycol, propylene glycol, glycerol, sorbitol, and polyethylene glycol.

[0034] Nitrogen-containing heterocyclic compounds, sulfonate compounds, and polyol compounds all possess polar functional groups and electron-rich active sites. During cathodic polarization, they can preferentially adsorb onto the newly formed gold deposition interface through electron donor-acceptor interactions, forming a dynamic adsorption layer. This layer selectively covers the cathodic active sites, regulates the discharge reduction rate and surface diffusion behavior of gold ions, inhibits abnormal grain growth caused by local rapid deposition, and reduces the accumulation of residual internal stress during high-thickness deposition. Consequently, it promotes the continuous formation of a fine-grained, continuous, and dense microstructure in the gold coating.

[0035] In one embodiment, when the gold plating solution contains a nitrogen-containing heterocyclic compound, step S3 includes: S3.1 Add gold salt, sodium sulfite, and nitrogen-containing heterocyclic compound to deionized water and stir at 300~500 rpm and 25~40℃ until completely dissolved to obtain gold plating solution, wherein the gold plating solution contains 5~20 g / L gold salt, 30~80 g / L sodium sulfite and 1~5 g / L nitrogen-containing heterocyclic compound.

[0036] S3.2. Place the substrate to be gold-plated in a gold plating solution with a temperature of 50~60℃ and a pH of 8.0~10.5, at a concentration of 0.2~1.0 A / dm³. 2 Gold plating is performed until the gold layer thickness is ≥30µ″ to obtain the treated substrate.

[0037] S3.3. Take out the substrate, wash and dry it with deionized water to obtain the gold-plated substrate. The temperature of the deionized water is 20~40℃, the washing time is 30~120s, and the drying temperature is 40~60℃.

[0038] S3.4. Immerse the gold-plated substrate in the stripping solution at 40~80℃ for 30~60 minutes, then rinse with deionized water and dry at 50~100℃ for 10~60 minutes to obtain a contact terminal with a high-thickness gold layer. The mass ratio of the gold-plated substrate to the stripping solution is 1:(5~10).

[0039] In one embodiment, when the gold plating solution contains a sulfonate compound, step S3 includes: S3.1 Add gold salt, sodium sulfite, and sulfonate compound to deionized water and stir at 300~500 rpm and 25~40℃ until completely dissolved to obtain gold plating solution, wherein the gold plating solution contains 5~20 g / L gold salt, 30~80 g / L sodium sulfite and 1~8 g / L sulfonate compound; S3.2. Place the substrate to be plated in a gold plating solution with a temperature of 55~75℃ and a pH of 8.5~10.5, at a flux of 0.8~2.5A / dm³. 2 Gold plating is performed until the gold layer thickness is ≥30µ″ to obtain the treated substrate; S3.3. Take out the substrate, wash and dry it with deionized water to obtain the gold-plated substrate. The temperature of the deionized water is 20~40℃, the washing time is 30~120s, and the drying temperature is 40~60℃. S3.4. Immerse the gold-plated substrate in the stripping solution at 40~80℃ for 30~60 minutes, then rinse with deionized water and dry at 50~100℃ for 10~60 minutes to obtain a contact terminal with a high-thickness gold layer. The mass ratio of the gold-plated substrate to the stripping solution is 1:(5~10).

[0040] In one embodiment, when the gold plating solution contains a polyol compound, step S3 includes: S3.1 Add gold salt, sodium sulfite, and polyol compound to deionized water and stir at 300~500 rpm and 25~40℃ until completely dissolved to obtain gold plating solution, wherein the gold plating solution contains 5~20 g / L gold salt, 30~80 g / L sodium sulfite and 1~10 g / L polyol compound; S3.2. Place the substrate to be plated in a gold plating solution with a temperature of 55~75℃ and a pH of 8.5~10.5, at a flux of 0.5~2.0 A / dm³. 2 Gold plating is performed until the gold layer thickness is ≥30µ″ to obtain the treated substrate; S3.3. Take out the substrate, wash and dry it with deionized water to obtain the gold-plated substrate. The temperature of the deionized water is 20~40℃, the washing time is 30~120s, and the drying temperature is 40~60℃. S3.4. Immerse the gold-plated substrate in the stripping solution at 40~80℃ for 30~60 minutes, then rinse with deionized water and dry at 50~100℃ for 10~60 minutes to obtain a contact terminal with a high-thickness gold layer. The mass ratio of the gold-plated substrate to the stripping solution is 1:(5~10).

[0041] In the above process, the gold salt includes at least one of sodium gold sulfite, potassium gold sulfite, and potassium gold citrate, and the stripping solution includes at least one of N-methylpyrrolidone, dimethyl sulfoxide, acetone, ethyl acetate, and γ-butyrolactone.

[0042] Furthermore, when gold plating is performed simultaneously using gold plating solutions containing nitrogen-containing heterocyclic compounds, sulfonate compounds, and polyol compounds respectively, step S3 further includes: S3.1 Add gold salt and sodium sulfite to deionized water and stir at 300~500 rpm and 25~40℃ until completely dissolved to obtain the gold plating solution. Then, add nitrogen-containing heterocyclic compound, sulfonate compound and polyol compound to the gold plating solution and stir to dissolve to obtain the first gold plating solution, the second gold plating solution and the third gold plating solution. The gold plating solution contains 5~20 g / L gold salt and 30~80 g / L sodium sulfite. The first gold plating solution contains 1~5 g / L nitrogen-containing heterocyclic compound. The second gold plating solution contains 1~8 g / L sulfonate compound. The third gold plating solution contains 1~10 g / L polyol compound. S3.2. Place the substrate to be gold-plated in the first gold plating solution with a temperature of 50~60℃ and a pH of 8.0~10.5, at a concentration of 0.2~1.0 A / dm³. 2 Gold nucleation treatment is performed until the gold layer thickness is 1~5 μ″ to obtain a primary processed substrate; S3.3. Place the primary treated substrate in a second gold plating solution with a temperature of 55~75℃ and a pH of 8.5~10.5, at a concentration of 0.8~2.5 A / dm³. 2 The gold layer is thickened to a thickness of 10~20 μ″ to obtain a secondary processed substrate. S3.4. Place the secondary-treated substrate in a third gold plating solution with a temperature of 55~75℃ and a pH of 8.5~10.5, at a concentration of 0.5~2.0 A / dm³. 2 The gold layer is leveled until the gold layer thickness is ≥30µ″, resulting in a three-stage treated substrate. S3.5. Take out the substrate after the three treatments, wash and dry it with deionized water to obtain the gold-plated substrate. The temperature of the deionized water is 20~40℃, the washing time is 30~120s, and the drying temperature is 40~60℃. S3.6. Immerse the gold-plated substrate in the stripping solution at 40~80℃ for 30~60 minutes, then rinse with deionized water and dry at 50~100℃ for 10~60 minutes to obtain a contact terminal with a high-thickness gold layer. The mass ratio of the gold-plated substrate to the stripping solution is 1:(5~10).

[0043] Gold plating was performed in stages using plating solutions containing nitrogen-containing heterocyclic compounds, sulfonate compounds, and polyol compounds, according to different growth stages of the gold plating layer. Nitrogen-containing heterocyclic compounds acted in the initial nucleation stage, promoting uniform nucleation of gold atoms and forming high-density fine-grained nuclei. Sulfonate compounds acted in the intermediate thickening stage, regulating gold ion mass transfer and grain growth rate, ensuring the gold plating layer remained dense and uniform during continuous thickening and reducing internal stress accumulation. Polyol compounds acted in the final leveling stage, selectively adsorbing onto raised areas of the plating surface, reducing the deposition rate in raised areas and promoting continuous growth in low-lying areas, thus improving the surface smoothness of the gold plating layer. The three plating solutions acted sequentially according to the gold plating layer growth pattern, achieving progressive optimization of grain structure, microstructure density, and surface morphology. This enabled the formation of a high-thickness gold plating layer through continuous synergistic regulation from uniform nucleation and stable thickening to surface leveling, further enhancing the conductivity of contact terminals containing high-thickness gold layers.

[0044] In addition, a contact terminal with a high-thickness gold layer is also provided, which is prepared by the above-described method for preparing a contact terminal with a high-thickness gold layer.

[0045] For example, the present invention provides the following specific embodiments to illustrate the specific preparation method: Example 1: S1.1 Place the copper alloy terminal substrate in an alkaline degreasing solution and degrease it at 60°C for 6 minutes. Then wash it with water to obtain the degreased terminal. The alkaline degreasing solution consists of 20 g / L sodium hydroxide, 40 g / L sodium carbonate, 2 g / L sodium dodecyl sulfate and the remainder is deionized water. S1.2 Place the degreased terminals in a deionized aqueous solution containing 15 vol% hydrochloric acid, activate at room temperature for 75 s, wash with water to obtain activated terminals; S1.3. Place the activated terminal in a nickel plating solution at a temperature of 50℃ and a pH of 4.0, at a concentration of 1 A / dm³. 2 The current density was deposited to a nickel layer thickness of 20 μ″, and then the current density was increased to 2.0 A / dm. 2 The temperature of the nickel plating bath was controlled to rise to 55°C, and deposition continued until the nickel layer thickness reached 50 μm; finally, the current density was increased to 4.0 A / dm². 2 The temperature of the nickel plating solution was raised to 60°C, and deposition continued until the total thickness of the nickel layer reached 100 μ″, resulting in a pretreated substrate containing a nickel layer. The nickel plating solution consisted of 220 g / L nickel chloride, 32 g / L boric acid, 35 g / L citric acid, and the remainder deionized water. S2.1. Polyurethane resin and hexamethylene diisocyanate trimer curing agent are added to acetone and stirred at 32°C and 450 rpm to dissolve, thereby obtaining a resin coating solution. The mass ratio of polyurethane resin to acetone is 1:1.5, and the amount of curing agent added is 10 wt% of the mass of polyurethane resin. S2.2 Apply the resin coating liquid to the non-gold plating area of ​​the pretreated substrate containing the nickel layer, and cure at 90°C for 60 min to obtain the substrate to be gold plated. The coating thickness of the resin coating liquid is 30 μm. S3.1 Add sodium gold sulfite, sodium sulfite, and imidazole to deionized water and stir at 400 rpm and 32°C until completely dissolved to obtain a gold plating solution containing 12 g / L sodium gold sulfite, 50 g / L sodium sulfite, and 3 g / L imidazole. S3.2. Place the substrate to be gold-plated in a gold plating solution at a temperature of 55℃ and a pH of 9.5, with a flux of 0.6A / dm³. 2 Gold plating is performed until the gold layer thickness is 30µ″ to obtain the treated substrate; S3.3. Take out the substrate, wash and dry it with deionized water to obtain the gold-plated substrate. The temperature of the deionized water is 30℃, the washing time is 75s, and the drying temperature is 50℃. S3.4. Immerse the gold-plated substrate in N-methylpyrrolidone at 60°C for 45 minutes, then rinse with deionized water and dry at 80°C for 30 minutes to obtain a contact terminal with a high-thickness gold layer. The mass ratio of the gold-plated substrate to N-methylpyrrolidone is 1:8.

[0046] Example 2: S1.1 Place the copper alloy terminal substrate in an alkaline degreasing solution and degrease it at 60°C for 6 minutes. Then wash it with water to obtain the degreased terminal. The alkaline degreasing solution consists of 20 g / L sodium hydroxide, 40 g / L sodium carbonate, 2 g / L sodium dodecyl sulfate and the remainder is deionized water. S1.2 Place the degreased terminals in a deionized aqueous solution containing 15 vol% hydrochloric acid, activate at room temperature for 75 s, wash with water to obtain activated terminals; S1.3. Place the activated terminal in a nickel plating solution at a temperature of 50℃ and a pH of 4.0, at a concentration of 1 A / dm³. 2 The current density was deposited to a nickel layer thickness of 20 μ″, and then the current density was increased to 2.0 A / dm. 2 The temperature of the nickel plating bath was controlled to rise to 55°C, and deposition continued until the nickel layer thickness reached 50 μm; finally, the current density was increased to 4.0 A / dm². 2The temperature of the nickel plating solution was raised to 60°C, and deposition continued until the total thickness of the nickel layer reached 100 μ″, resulting in a pretreated substrate containing a nickel layer. The nickel plating solution consisted of 220 g / L nickel chloride, 32 g / L boric acid, 35 g / L citric acid, and the remainder deionized water. S2.1. Polyurethane resin and hexamethylene diisocyanate trimer curing agent are added to acetone and stirred at 32°C and 450 rpm to dissolve, thereby obtaining a resin coating solution. The mass ratio of polyurethane resin to acetone is 1:1.5, and the amount of curing agent added is 10 wt% of the mass of polyurethane resin. S2.2 Apply the resin coating liquid to the non-gold plating area of ​​the pretreated substrate containing the nickel layer, and cure at 90°C for 60 min to obtain the substrate to be gold plated. The coating thickness of the resin coating liquid is 30 μm. S3.1 Add sodium gold sulfite, sodium sulfite, and sodium hydroxyethanesulfonate to deionized water and stir at 400 rpm and 32°C until completely dissolved to obtain a gold plating solution containing 12 g / L sodium gold sulfite, 50 g / L sodium sulfite, and 5 g / L sodium hydroxyethanesulfonate. S3.2. Place the substrate to be gold-plated in a gold plating solution at a temperature of 65℃ and a pH of 9.5, with a flux of 1.6A / dm³. 2 Gold plating is performed until the gold layer thickness is 30µ″ to obtain the treated substrate; S3.3. Take out the substrate, wash and dry it with deionized water to obtain the gold-plated substrate. The temperature of the deionized water is 30℃, the washing time is 75s, and the drying temperature is 50℃. S3.4. Immerse the gold-plated substrate in N-methylpyrrolidone at 60°C for 45 minutes, then rinse with deionized water and dry at 80°C for 30 minutes to obtain a contact terminal with a high-thickness gold layer. The mass ratio of the gold-plated substrate to N-methylpyrrolidone is 1:8.

[0047] Example 3: S1.1 Place the copper alloy terminal substrate in an alkaline degreasing solution and degrease it at 60°C for 6 minutes. Then wash it with water to obtain the degreased terminal. The alkaline degreasing solution consists of 20 g / L sodium hydroxide, 40 g / L sodium carbonate, 2 g / L sodium dodecyl sulfate and the remainder is deionized water. S1.2 Place the degreased terminals in a deionized aqueous solution containing 15 vol% hydrochloric acid, activate at room temperature for 75 s, wash with water to obtain activated terminals; S1.3. Place the activated terminal in a nickel plating solution at a temperature of 50℃ and a pH of 4.0, at a concentration of 1 A / dm³. 2 The current density was deposited to a nickel layer thickness of 20 μ″, and then the current density was increased to 2.0 A / dm. 2The temperature of the nickel plating bath was controlled to rise to 55°C, and deposition continued until the nickel layer thickness reached 50 μm; finally, the current density was increased to 4.0 A / dm². 2 The temperature of the nickel plating solution was raised to 60°C, and deposition continued until the total thickness of the nickel layer reached 100 μ″, resulting in a pretreated substrate containing a nickel layer. The nickel plating solution consisted of 220 g / L nickel chloride, 32 g / L boric acid, 35 g / L citric acid, and the remainder deionized water. S2.1. Polyurethane resin and hexamethylene diisocyanate trimer curing agent are added to acetone and stirred at 32°C and 450 rpm to dissolve, thereby obtaining a resin coating solution. The mass ratio of polyurethane resin to acetone is 1:1.5, and the amount of curing agent added is 10 wt% of the mass of polyurethane resin. S2.2 Apply the resin coating liquid to the non-gold plating area of ​​the pretreated substrate containing the nickel layer, and cure at 90°C for 60 min to obtain the substrate to be gold plated. The coating thickness of the resin coating liquid is 30 μm. S3.1 Add sodium gold sulfite, sodium sulfite and sorbitol to deionized water, stir at 400 rpm and 32℃ until completely dissolved to obtain gold plating solution, wherein the gold plating solution contains 12 g / L sodium gold sulfite, 50 g / L sodium sulfite and 5 g / L sorbitol. S3.2. Place the substrate to be plated in a gold plating solution at a temperature of 65℃ and a pH of 9.5, with a flux of 1.2A / dm³. 2 Gold plating is performed until the gold layer thickness is 30µ″ to obtain the treated substrate; S3.3. Take out the substrate, wash and dry it with deionized water to obtain the gold-plated substrate. The temperature of the deionized water is 30℃, the washing time is 75s, and the drying temperature is 50℃. S3.4. Immerse the gold-plated substrate in N-methylpyrrolidone at 60°C for 45 minutes, then rinse with deionized water and dry at 80°C for 30 minutes to obtain a contact terminal with a high-thickness gold layer. The mass ratio of the gold-plated substrate to N-methylpyrrolidone is 1:8.

[0048] Example 4: S1.1 Place the copper alloy terminal substrate in an alkaline degreasing solution and degrease it at 60°C for 6 minutes. Then wash it with water to obtain the degreased terminal. The alkaline degreasing solution consists of 20 g / L sodium hydroxide, 40 g / L sodium carbonate, 2 g / L sodium dodecyl sulfate and the remainder is deionized water. S1.2 Place the degreased terminals in a deionized aqueous solution containing 15 vol% hydrochloric acid, activate at room temperature for 75 s, wash with water to obtain activated terminals; S1.3. Place the activated terminal in a nickel plating solution at a temperature of 50℃ and a pH of 4.0, at a concentration of 1 A / dm³. 2The current density was deposited to a nickel layer thickness of 20 μ″, and then the current density was increased to 2.0 A / dm. 2 The temperature of the nickel plating bath was controlled to rise to 55°C, and deposition continued until the nickel layer thickness reached 50 μm; finally, the current density was increased to 4.0 A / dm². 2 The temperature of the nickel plating solution was raised to 60°C, and deposition continued until the total thickness of the nickel layer reached 100 μ″, resulting in a pretreated substrate containing a nickel layer. The nickel plating solution consisted of 220 g / L nickel chloride, 32 g / L boric acid, 35 g / L citric acid, and the remainder deionized water. S2.1. Polyurethane resin and hexamethylene diisocyanate trimer curing agent are added to acetone and stirred at 32°C and 450 rpm to dissolve, thereby obtaining a resin coating solution. The mass ratio of polyurethane resin to acetone is 1:1.5, and the amount of curing agent added is 10 wt% of the mass of polyurethane resin. S2.2 Apply the resin coating liquid to the non-gold plating area of ​​the pretreated substrate containing the nickel layer, and cure at 90°C for 60 min to obtain the substrate to be gold plated. The coating thickness of the resin coating liquid is 30 μm. S3.1 Add gold salt and sodium sulfite to deionized water and stir at 400 rpm and 32°C until completely dissolved to obtain the gold plating solution. Then add imidazole, sodium hydroxyethanesulfonate and sorbitol to the gold plating solution and stir to dissolve to obtain the first gold plating solution, the second gold plating solution and the third gold plating solution. The gold plating solution contains 12 g / L gold salt and 50 g / L sodium sulfite. The first gold plating solution contains 3 g / L imidazole. The second gold plating solution contains 5 g / L sodium hydroxyethanesulfonate. The third gold plating solution contains 5 g / L sorbitol. S3.2. Place the substrate to be gold-plated in the first gold plating solution at a temperature of 55℃ and a pH of 9.5, with a flux of 0.6A / dm³. 2 Gold plating is performed until the gold layer thickness is 3µ″, resulting in a primary processed substrate; S3.3. Place the primary treated substrate in a second gold plating solution at a temperature of 65℃ and a pH of 9.5, at a concentration of 1.6 A / dm³. 2 Gold plating is performed until the gold layer thickness is 15µ″, resulting in a secondary processed substrate. S3.4. Place the secondary-treated substrate in a third gold plating solution at a temperature of 65℃ and a pH of 9.5, at a concentration of 1.2 A / dm³. 2 Gold plating was performed until the gold layer thickness was 30 μ″, resulting in a substrate with three treatments. S3.5. Take out the substrate after the three treatments, wash and dry it with deionized water to obtain the gold-plated substrate. The temperature of the deionized water is 30℃, the washing time is 75s, and the drying temperature is 50℃. S3.6. Immerse the gold-plated substrate in N-methylpyrrolidone at 60°C for 45 minutes, then rinse with deionized water and dry at 80°C for 30 minutes to obtain a contact terminal with a high-thickness gold layer. The mass ratio of the gold-plated substrate to N-methylpyrrolidone is 1:8.

[0049] Comparative Example 1: S1.1 Place the copper alloy terminal substrate in an alkaline degreasing solution and degrease it at 60°C for 6 minutes. Then wash it with water to obtain the degreased terminal. The alkaline degreasing solution consists of 20 g / L sodium hydroxide, 40 g / L sodium carbonate, 2 g / L sodium dodecyl sulfate and the remainder is deionized water. S1.2 Place the degreased terminals in a deionized aqueous solution containing 15 vol% hydrochloric acid, activate at room temperature for 75 s, wash with water to obtain activated terminals; S1.3. Place the activated terminal in a nickel plating solution at a temperature of 50℃ and a pH of 4.0, at a concentration of 1 A / dm³. 2 The current density was deposited to a nickel layer thickness of 20 μ″, and then the current density was increased to 2.0 A / dm. 2 The temperature of the nickel plating bath was controlled to rise to 55°C, and deposition continued until the nickel layer thickness reached 50 μm; finally, the current density was increased to 4.0 A / dm². 2 The temperature of the nickel plating solution was raised to 60°C, and deposition continued until the total thickness of the nickel layer reached 100 μ″, resulting in a pretreated substrate containing a nickel layer. The nickel plating solution consisted of 220 g / L nickel chloride, 32 g / L boric acid, 35 g / L citric acid, and the remainder deionized water. S2.1. Polyurethane resin and hexamethylene diisocyanate trimer curing agent are added to acetone and stirred at 32°C and 450 rpm to dissolve, thereby obtaining a resin coating solution. The mass ratio of polyurethane resin to acetone is 1:1.5, and the amount of curing agent added is 10 wt% of the mass of polyurethane resin. S2.2 Apply the resin coating liquid to the non-gold plating area of ​​the pretreated substrate containing the nickel layer, and cure at 90°C for 60 min to obtain the substrate to be gold plated. The coating thickness of the resin coating liquid is 30 μm. S3.1 Add sodium gold sulfite and sodium sulfite to deionized water and stir at 400 rpm and 32°C until completely dissolved to obtain a gold plating solution containing 12 g / L sodium gold sulfite and 50 g / L sodium sulfite. S3.2. Place the substrate to be gold-plated in a gold plating solution at a temperature of 55℃ and a pH of 9.5, with a flux of 0.6A / dm³. 2 Gold plating is performed until the gold layer thickness is 30µ″ to obtain the treated substrate; S3.3. Take out the substrate, wash and dry it with deionized water to obtain the gold-plated substrate. The temperature of the deionized water is 30℃, the washing time is 75s, and the drying temperature is 50℃. S3.4. Immerse the gold-plated substrate in N-methylpyrrolidone at 60°C for 45 minutes, then rinse with deionized water and dry at 80°C for 30 minutes to obtain a contact terminal with a high-thickness gold layer. The mass ratio of the gold-plated substrate to N-methylpyrrolidone is 1:8.

[0050] The process is basically the same as in Example 1, except that the gold plating solution in step S3 does not contain imidazole, that is, no nitrogen-containing heterocyclic compound is used in step S3.

[0051] Comparative Example 2: S1.1 Place the copper alloy terminal substrate in an alkaline degreasing solution and degrease it at 60°C for 6 minutes. Then wash it with water to obtain the degreased terminal. The alkaline degreasing solution consists of 20 g / L sodium hydroxide, 40 g / L sodium carbonate, 2 g / L sodium dodecyl sulfate and the remainder is deionized water. S1.2 Place the degreased terminals in a deionized aqueous solution containing 15 vol% hydrochloric acid, activate at room temperature for 75 s, wash with water to obtain activated terminals; S1.3. Place the activated terminal in a nickel plating solution at a temperature of 50℃ and a pH of 4.0, at a concentration of 1 A / dm³. 2 The current density was deposited to a nickel layer thickness of 20 μ″, and then the current density was increased to 2.0 A / dm. 2 The temperature of the nickel plating bath was controlled to rise to 55°C, and deposition continued until the nickel layer thickness reached 50 μm; finally, the current density was increased to 4.0 A / dm². 2 The temperature of the nickel plating solution was raised to 60°C, and deposition continued until the total thickness of the nickel layer reached 100 μ″, resulting in a pretreated substrate containing a nickel layer. The nickel plating solution consisted of 220 g / L nickel chloride, 32 g / L boric acid, 35 g / L citric acid, and the remainder deionized water. S2.1. Polyurethane resin and hexamethylene diisocyanate trimer curing agent are added to acetone and stirred at 32°C and 450 rpm to dissolve, thereby obtaining a resin coating solution. The mass ratio of polyurethane resin to acetone is 1:1.5, and the amount of curing agent added is 10 wt% of the mass of polyurethane resin. S2.2 Apply the resin coating liquid to the non-gold plating area of ​​the pretreated substrate containing the nickel layer, and cure at 90°C for 60 min to obtain the substrate to be gold plated. The coating thickness of the resin coating liquid is 30 μm. S3.1 Add sodium gold sulfite and sodium sulfite to deionized water and stir at 400 rpm and 32°C until completely dissolved to obtain a gold plating solution containing 12 g / L sodium gold sulfite and 50 g / L sodium sulfite. S3.2. Place the substrate to be plated with gold in a gold plating solution at a temperature of 55℃ and a pH of 9.5, and perform gold plating using a gradient current electroplating process, initially at 0.4A / dm³. 2 Gold plating was performed until the gold layer thickness reached 8µ″, and then the current density was increased to 0.7A / dm². 2 Continue gold plating until the gold layer thickness reaches 18µ″, and finally increase the current density to 1.0A / dm. 2 Continue gold plating until the gold layer thickness reaches 30µ″, and the treated substrate is obtained; S3.3. Take out the substrate, wash and dry it with deionized water to obtain the gold-plated substrate. The temperature of the deionized water is 30℃, the washing time is 75s, and the drying temperature is 50℃. S3.4. Immerse the gold-plated substrate in N-methylpyrrolidone at 60°C for 45 minutes, then rinse with deionized water and dry at 80°C for 30 minutes to obtain a contact terminal with a high-thickness gold layer. The mass ratio of the gold-plated substrate to N-methylpyrrolidone is 1:8.

[0052] The process is basically the same as in Example 1, except that the gold plating solution in step S3 does not contain imidazole, that is, nitrogen-containing heterocyclic compounds are not used in step S3, but gradient current density is used for electroplating gold.

[0053] Comparative Example 3: S1.1 Place the copper alloy terminal substrate in an alkaline degreasing solution and degrease it at 60°C for 6 minutes. Then wash it with water to obtain the degreased terminal. The alkaline degreasing solution consists of 20 g / L sodium hydroxide, 40 g / L sodium carbonate, 2 g / L sodium dodecyl sulfate and the remainder is deionized water. S1.2 Place the degreased terminals in a deionized aqueous solution containing 15 vol% hydrochloric acid, activate at room temperature for 75 s, wash with water to obtain activated terminals; S1.3. Place the activated terminal in a nickel plating solution at a temperature of 50℃ and a pH of 4.0, at a concentration of 1 A / dm³. 2 The current density was deposited to a nickel layer thickness of 20 μ″, and then the current density was increased to 2.0 A / dm. 2 The temperature of the nickel plating bath was controlled to rise to 55°C, and deposition continued until the nickel layer thickness reached 50 μm; finally, the current density was increased to 4.0 A / dm². 2The temperature of the nickel plating solution was raised to 60°C, and deposition continued until the total thickness of the nickel layer reached 100 μ″, resulting in a pretreated substrate containing a nickel layer. The nickel plating solution consisted of 220 g / L nickel chloride, 32 g / L boric acid, 35 g / L citric acid, and the remainder deionized water. S2. Fix the pretreated substrate containing the nickel layer in the positioning fixture, align the contact area with the mask opening, and then cover the surface of the pretreated substrate with a stainless steel mask with a thickness of 0.20 mm. Apply a clamping pressure of 0.4 MPa using an elastic clamping mechanism to make the mask fit tightly against the surface of the pretreated substrate, exposing only the area to be gold plated, thus obtaining the substrate to be gold plated. The size of the mask opening is 0.05 mm larger than the area to be gold plated on one side, and the positioning accuracy between the mask and the pretreated substrate is controlled within ±0.02 mm. S3.1 Add sodium gold sulfite, sodium sulfite, and imidazole to deionized water and stir at 400 rpm and 32°C until completely dissolved to obtain a gold plating solution containing 12 g / L sodium gold sulfite, 50 g / L sodium sulfite, and 3 g / L imidazole. S3.2. Place the substrate to be gold-plated in a gold plating solution at a temperature of 55℃ and a pH of 9.5, with a flux of 0.6A / dm³. 2 Gold plating is performed until the gold layer thickness is 30µ″ to obtain the treated substrate; S3.3. Remove the substrate, wash and dry it with deionized water to obtain a contact terminal with a high-thickness gold layer. The deionized water temperature is 30°C, the cleaning time is 75s, and the drying temperature is 50°C.

[0054] The process is basically the same as in Example 1, except that the masking method in step S2 is physical masking, and no resin insulating material is used for masking.

[0055] Performance testing: Contact resistance: The contact resistance of the sample terminals prepared in Examples 1-4 and Comparative Examples 1-3 was measured using a four-probe resistance tester. Each sample was measured 3 times and the average value was taken. The test data are shown in Table 1.

[0056] Table 1 Contact resistance of contact terminals: As shown in Table 1, the contact resistance of the contact terminals prepared in Examples 1-4 is lower than that of Comparative Examples 1-3. Examples 1-3 used gold plating solutions containing nitrogen-containing heterocyclic compounds, sulfonate compounds, or polyol compounds, respectively, which all reduced the contact resistance of the contact terminals. Example 4 used a first, second, and third gold plating solution sequentially for segmented gold plating, further reducing the contact resistance to levels lower than those in Examples 1-3. This indicates that the phased use of different gold plating solutions can further improve the conductivity of contact terminals containing a high-thickness gold layer. Comparative Example 1, without any functional additives, had the highest contact resistance. Comparative Example 2, although using a gradient current electroplating process, still had a higher contact resistance than Examples 1-4. Comparative Example 3, after using a physical mask method, also had a higher contact resistance than Examples 1-4. This demonstrates that the preparation method of this application can effectively reduce the contact resistance of the contact terminals and improve their conductivity.

[0057] Insertion and removal resistance test: The contact terminals prepared in Example 1 and Comparative Example 3 were assembled with the corresponding mating terminals. Under an environment of 23±2℃ and relative humidity of 50±5%, the insertion and removal cycles were performed using an insertion and removal life tester at an insertion and removal speed of 60±10mm / min. The insertion and removal stroke was based on the complete insertion and complete separation of the terminals. 100, 500, 1000, and 3000 insertion and removal cycles were completed respectively. After each set number of cycles, the terminals were re-inserted to the rated position and the rated contact force was applied. The contact resistance was measured using a micro-ohmmeter with the four-terminal method (Kelvin method) and the test current was 100mA. Each sample was measured 5 times consecutively and the average value was taken. No less than 10 samples were tested in each group, and the average value was taken as the contact resistance of the group of samples. The test data are shown in Table 2.

[0058] Table 2 Insertion and Removal Resistance Test Test results show that the contact terminal prepared in Example 1 has a low contact resistance in the initial state, and the increase in contact resistance is small as the number of insertions and removals increases; while when gold plating is performed using a physical mask in Comparative Example 3, the small gap between the mask and the nickel layer surface can easily lead to abnormal gold deposition in the boundary area during the gold plating process, resulting in uneven local plating structure. During repeated insertions and removals, the boundary area is more prone to wear and interface failure, leading to a continuous increase in contact resistance.

[0059] Other embodiments of this disclosure will readily occur to those skilled in the art upon consideration of the specification and practice of the invention disclosed herein. This application is intended to cover any variations, uses, or adaptations of this disclosure that follow the general principles of this disclosure and include common knowledge or customary techniques in the art not disclosed herein. The specification and examples are to be considered exemplary only, and the true scope and spirit of this disclosure are indicated by the following claims.

Claims

1. A method for preparing a contact terminal containing a high-thickness gold layer, characterized in that, The preparation method includes the following preparation steps: S1. After surface treatment of the terminal substrate, it is placed in a nickel plating solution and nickel plating is performed using a gradient current method to obtain a pretreated substrate containing a nickel layer. In the gradient current method, the current density increases with the increase of the nickel layer thickness. S2. Coat the non-gold-plated areas of the pretreated substrate containing a nickel layer with a resin insulating material to obtain the substrate to be gold-plated. S3. The substrate to be gold-plated is placed in the gold plating solution for gold plating treatment. After the gold plating is completed, the insulating protective layer is removed to obtain a contact terminal with a high-thickness gold layer. The gold plating solution includes at least one of nitrogen-containing heterocyclic compounds, sulfonate compounds, and polyol compounds.

2. The method for preparing a contact terminal with a high-thickness gold layer according to claim 1, characterized in that, In step S1, the terminal substrate is a copper alloy substrate, and the nickel plating solution consists of 150~300g / L of nickel salt, 25~40g / L of boric acid, 20~50g / L of citric acid, and the remainder of deionized water. The nickel salt includes at least one of nickel aminosulfonate, nickel sulfate, and nickel chloride.

3. The method for preparing a contact terminal with a high-thickness gold layer according to claim 2, characterized in that, Step S1 includes: S1.1 Place the terminal substrate in an alkaline degreasing solution and degrease it at 50~70℃ for 3~10 minutes, then wash it with water to obtain a degreased terminal. The alkaline degreasing solution is composed of 10~30g / L sodium hydroxide, 20~60g / L sodium carbonate, 0.5~3g / L surfactant and the balance deionized water. The surfactant includes at least one of fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, sodium dodecyl sulfate and sodium dodecylbenzene sulfonate. S1.2 Place the degreased terminals in the activation solution and activate them at room temperature for 30~120s. Wash with water to obtain activated terminals. The activation solution is a deionized aqueous solution containing 10~20 vol% hydrochloric acid or 5~15 vol% sulfuric acid. S1.

3. Place the activated terminal in a nickel plating solution with a temperature of 45~55℃ and a pH of 3.8~4.5, at a flux of 0.5~1.5A / dm³. 2 The current density was deposited to a nickel layer thickness of 10~30 μ″, and then the current density was increased to 1.5~2.5 A / dm. 2 The temperature of the nickel plating bath was controlled to rise to 50-60℃, and deposition continued until the nickel layer thickness reached 30-80 μm; finally, the current density was increased to 3.0-5.0 A / dm². 2 The temperature of the nickel plating solution is raised to 55~65℃, and deposition continues until the total thickness of the nickel layer reaches 50~150µ″, thus obtaining a pretreated substrate containing a nickel layer.

4. The method for preparing a contact terminal with a high-thickness gold layer according to claim 1, characterized in that, The resin insulation material in step S2 includes at least one of polyurethane resin, epoxy resin, and acrylic resin.

5. The method for preparing a contact terminal with a high-thickness gold layer according to claim 4, characterized in that, Step S2 includes: S2.1 Add the resin insulating material and curing agent to an organic solvent, stir and dissolve at 25~40℃ and 300~600rpm to obtain a resin coating solution. The organic solvent includes at least one of acetone, butanone, and anhydrous ethanol. The mass ratio of the resin insulating material to the organic solvent is 1:(1~2). The curing agent includes at least one of amine curing agent, isocyanate curing agent, and photocuring agent. The amount of curing agent added is 1~15wt% of the mass of the resin insulating material. S2.2 Apply the resin coating liquid to the non-gold plating area of ​​the pretreated substrate containing the nickel layer and cure it to obtain the substrate to be gold plated. The coating thickness of the resin coating liquid is 20~40μm.

6. The method for preparing a contact terminal with a high-thickness gold layer according to claim 1, characterized in that, In step S3, the nitrogen-containing heterocyclic compound includes at least one of imidazole, pyrazole, and triazole; the sulfonate compound includes at least one of sodium hydroxyethanesulfonate, sodium methanesulfonate, sodium ethanesulfonate, and sodium propanesulfonate; and the polyol compound includes at least one of ethylene glycol, propylene glycol, glycerol, sorbitol, and polyethylene glycol.

7. The method for preparing a contact terminal with a high-thickness gold layer according to claim 6, characterized in that, When the gold plating solution contains nitrogen-containing heterocyclic compounds, step S3 includes: S3.1 Add gold salt, sodium sulfite, and nitrogen-containing heterocyclic compound to deionized water, stir at 300~500 rpm and 25~40℃ until completely dissolved to obtain gold plating solution, wherein the gold plating solution contains 5~20 g / L gold salt, 30~80 g / L sodium sulfite and 1~5 g / L nitrogen-containing heterocyclic compound, and the gold salt includes at least one of sodium gold sulfite, potassium gold sulfite and potassium gold citrate; S3.

2. Place the substrate to be gold-plated in a gold plating solution with a temperature of 50~60℃ and a pH of 8.0~10.5, at a concentration of 0.2~1.0 A / dm³. 2 Gold plating is performed until the gold layer thickness is ≥30µ″ to obtain the treated substrate; S3.

3. Take out the substrate, wash and dry it with deionized water to obtain the gold-plated substrate. The temperature of the deionized water is 20~40℃, the washing time is 30~120s, and the drying temperature is 40~60℃. S3.4 Immerse the gold-plated substrate in the stripping solution at 40~80℃ for 30~60 minutes, then rinse with deionized water and dry at 50~100℃ for 10~60 minutes to obtain a contact terminal with a high-thickness gold layer. The mass ratio of the gold-plated substrate to the stripping solution is 1:(5~10). The stripping solution includes at least one of N-methylpyrrolidone, dimethyl sulfoxide, acetone, ethyl acetate, and γ-butyrolactone.

8. The method for preparing a contact terminal with a high-thickness gold layer according to claim 6, characterized in that, When the gold plating solution contains sulfonate compounds, step S3 includes: S3.1 Add gold salt, sodium sulfite, and sulfonate compound to deionized water and stir at 300-500 rpm and 25-40°C until completely dissolved to obtain a gold plating solution. The gold plating solution contains 5-20 g / L gold salt, 30-80 g / L sodium sulfite, and 1-8 g / L sulfonate compound. The gold salt includes at least one of sodium gold sulfite, potassium gold sulfite, and potassium gold citrate. S3.

2. Place the substrate to be plated in a gold plating solution with a temperature of 55~75℃ and a pH of 8.5~10.5, at a flux of 0.8~2.5A / dm³. 2 Gold plating is performed until the gold layer thickness is ≥30µ″ to obtain the treated substrate; S3.

3. Take out the substrate, wash and dry it with deionized water to obtain the gold-plated substrate. The temperature of the deionized water is 20~40℃, the washing time is 30~120s, and the drying temperature is 40~60℃. S3.4 Immerse the gold-plated substrate in the stripping solution at 40~80℃ for 30~60 minutes, then rinse with deionized water and dry at 50~100℃ for 10~60 minutes to obtain a contact terminal with a high-thickness gold layer. The mass ratio of the gold-plated substrate to the stripping solution is 1:(5~10). The stripping solution includes at least one of N-methylpyrrolidone, dimethyl sulfoxide, acetone, ethyl acetate, and γ-butyrolactone.

9. The method for preparing a contact terminal with a high-thickness gold layer according to claim 6, characterized in that, When the gold plating solution contains polyol compounds, step S3 includes: S3.1 Add gold salt, sodium sulfite, and polyol compound to deionized water and stir at 300-500 rpm and 25-40°C until completely dissolved to obtain a gold plating solution. The gold plating solution contains 5-20 g / L gold salt, 30-80 g / L sodium sulfite, and 1-10 g / L polyol compound. The gold salt includes at least one of sodium gold sulfite, potassium gold sulfite, and potassium gold citrate. S3.

2. Place the substrate to be plated in a gold plating solution with a temperature of 55~75℃ and a pH of 8.5~10.5, at a flux of 0.5~2.0 A / dm³. 2 Gold plating is performed until the gold layer thickness is ≥30µ″ to obtain the treated substrate; S3.

3. Take out the substrate, wash and dry it with deionized water to obtain the gold-plated substrate. The temperature of the deionized water is 20~40℃, the washing time is 30~120s, and the drying temperature is 40~60℃. S3.4 Immerse the gold-plated substrate in the stripping solution at 40~80℃ for 30~60 minutes, then rinse with deionized water and dry at 50~100℃ for 10~60 minutes to obtain a contact terminal with a high-thickness gold layer. The mass ratio of the gold-plated substrate to the stripping solution is 1:(5~10). The stripping solution includes at least one of N-methylpyrrolidone, dimethyl sulfoxide, acetone, ethyl acetate, and γ-butyrolactone.

10. A contact terminal containing a high-thickness gold layer, characterized in that, The contact terminal with a high-thickness gold layer is prepared by any one of the preparation methods of a contact terminal with a high-thickness gold layer as described in claims 1-9.